Da educação do rebanho : reflexões nietzschenianas sobre o ensino oferecido às massas - Marchesi, Reinaldo de Souza (2011)
Of Flock Education: nietzschean reflection on education offered to the masses‖ is the elected title to develop a research regarding the educational issue in Friedrich Nietzsche. Bearing the notion that multiple are the possible entries in his philosophy, in his view on education I found my entry, about which I raised the discussion on the superior education expansion discourse. The main objective was analyzing references from the philosopher‘s text, about his conceptions and critics, hypothetically aiming to figure out if what has been done in XIX century Germany has been quite present in what we see in our current educational system. I attempted to expose the reasons for which Nietzsche criticized the education of this time and his notes for a determined perspective of a superior education that would not be destined for all people, as in the democratizing forms which we behold today. As a methodological resource, the interpretation method is employed to accomplish a profitable reading of Nietzsche‘s writings, holding into analysis the Conferences ―Over the future of our educational establishments‖ pronounced in Basilea in the year of 1872. Having worked Nietzsche‘s philosophy as theoretic reference, his text has been used as the main source aiming to produce statements at his light or in the perspective of his thoughts. I also made use of experts‘ bibliographic production (commentator readers) of Nietzsche‘s work. Of results and discussions: in Nietzsche‘s reading, education is a ―flock‖ phenomena since his time, and it has been noticed that this has been radicalized even more until the XXI century under the reflexes of an Illuminist proposal of educational universalization inspired on the French Revolution. Also, from the moment the state seizes control of the educational system in Germany, as well as there, here it is also clear that the tendency to an education that instructs for only one profession gets on the way of an education intended to instruct for culture. Another fact is that education is put as a destiny that is common to all, and, when set forth that way, I implicitly see a totalitarian and totalizing idea present in such speech. The trend in vogue about professional ―success‖ via educational institutions is a discursive mechanism that aims to assure the flock‘s interest in the educational destiny which is offered to them, one way to ―flock them in‖. The fate created and projected by the State for the University (which would have to be par excellence a cultural institution) aims to offer an education of the laissez-faire kind (flattening differences/ homogenizing the different ones) capable to produce only two types of subjects: the professional ones – ―living-making servants‖ and/or the erudite ones – ―slaves to science‖, instead of offering an education towards culture which would produce creative individuals. In a metaphorical sense, we talked about education for the masses as flock education, where the totalizing attempt of it to be meant for all unfolds the reality of a lowquality education for all. Within the project of being meant for the majority, the sense of quality and the possibility of the goal of a true culture-bound formation are negotiated. We understand that to be the problem of the speech that is unable to be accomplished, good enough only for utopia.